2-D Protein Crystals as an Immobilization Matrix for Producing Reaction Zones in Dipstick-Style Immunoassays. (November 1996) - Breitwieser, A.; Küpcü, S.; Howorka, S.; Weigert, S.; Langer, C.; Hoffmann-Sommergruber, K.; Scheiner, O.; Sleytr, U.B.; Sára, M.
In the present study, the applicability of crystalline bacterial cell-surface layers (Slayers) as novel immobilization matrices and reaction zones for dipstick-style immunoassays was investigated. For this purpose, S-layer-carrying cell-wall fragments from Bacillus sphaericus CCM 2120 were deposited on a microporous support, and the Slayer protein was cross-linked with glutaraldehyde. For developing appropriate test systems, either human IgG was directly linked to the carboxylic acid groups from the S-layer protein or it was immobilized using Protein A or, after biotinylation, using streptavidin. A clear correlation was obtained between the amount of anti-human IgG applied and the absorbance values in the immunoassays. S-layers with covalently bound recombinant major birch pollen allergen were used for quantitative and semiquantitative determination of an antibody raised against it. Using S-layers as an immobilization matrix in comparison to amorphous polymers has advantages in that the closed monolayers of functional macromolecules on their outermost surface allows for strong signals in immunoassays, almost completely eliminates background and prevents diffusion.